2019
DOI: 10.1007/s11661-019-05268-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Main Elements (Zn, Mg, and Cu) on Hot Tearing Susceptibility During Direct-Chill Casting of 7xxx Aluminum Alloys

Abstract: New 7xxx aluminum alloys with high alloying contents are being designed, which could induce serious hot tearing defects during direct-chill (DC) casting. Among all factors affecting hot tearing of 7xxx alloys, undoubtedly alloying elements play a significant role. In this study, the effect of main alloying elements (Zn, Mg, and Cu) on hot tearing of grain-refined Al-xZn-yMg-zCu alloys was investigated by a dedicated hot tearing rating apparatus simulating the DC-casting process. It was found that the minimum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…The free growth model [12] developed by Greer et al is commonly used to determine the potency of particles. [13][14][15] Zhang et al further considered the importance of crystallographic matching by applying their edge-to-edge matching model to explain the effectiveness of grain refiners and have successfully applied this to Al and Mg alloys. [6,[16][17][18] More recently, Fan et al [19] explained the growth of grains by elucidating the mechanisms of heterogeneous nucleation by epitaxial growth from substrates.…”
Section: Metal Fusion Additive Manufacturing (Am) Ismentioning
confidence: 99%
“…The free growth model [12] developed by Greer et al is commonly used to determine the potency of particles. [13][14][15] Zhang et al further considered the importance of crystallographic matching by applying their edge-to-edge matching model to explain the effectiveness of grain refiners and have successfully applied this to Al and Mg alloys. [6,[16][17][18] More recently, Fan et al [19] explained the growth of grains by elucidating the mechanisms of heterogeneous nucleation by epitaxial growth from substrates.…”
Section: Metal Fusion Additive Manufacturing (Am) Ismentioning
confidence: 99%
“…It is easy to apply in conventional foundry practice without significant changes in processing equipment and procedures. Previous studies confirmed that the modification of main alloying elements and their contents had complex and/or even contradictory effects on the hot tear tendency of AleZneMgeCu alloys [11,23,24]. Krajewski [25] and S. Shin et al [26] pointed that extra high Zn level (>20 wt%) could effectively suppress the formation of hot tear during solidification, however, the high density induced by high Zn is not favoured for light-weight requirement.…”
Section: Introductionmentioning
confidence: 94%
“…Li et al [77] modified this T-shaped device to measure the size of the hot tears and load development of DC-cast billets. As shown in Fig.…”
Section: Dedicated Hot Tearing Tests Simulating DC Castingmentioning
confidence: 99%
“…2.5. Importantly, this device provides information on the hot tearing susceptibility and load developments, and it has been applied to different AA7xxx alloys [26,[76][77][78]. Recently, Pan et al [79] replaced the T-shaped graphite mould with a bronze mould to obtain higher cooling rates ranging from 11 to 24 K/s to further simulate the solidification during fusion welding.…”
Section: Dedicated Hot Tearing Tests Simulating DC Castingmentioning
confidence: 99%